2010
DOI: 10.2478/v10042-010-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings in cornea tissue of patients with penetrating keratoplasty.

Abstract: Abstract:The aim of this clinical study was to examine corneas extracted from the patients during penetrating keratoplasty for the presence of immunoglobulins and inflammatory cells that can be warning for the graft failure. Individual clinical diagnoses were correlated to the presence of the inflammatory signs in corneal tissue. The signs of inflammation in corneal layers were detected especially in group of patients classified as viral keratitis but were also found in corneas of patients with degenerative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…36,37 Immune infiltrates are usually seen along multiple suture tracks, along the host side of the graft-host interface, and have no overlying epithelial defect compared with infectious infiltrates. 38 The treatment of suture-related infections begins with removal and culture of the suture. Running sutures pose a particular challenge as premature removal of the suture prior to proper would healing can lead to wound dehiscence.…”
Section: Suture-related Complicationsmentioning
confidence: 99%
“…36,37 Immune infiltrates are usually seen along multiple suture tracks, along the host side of the graft-host interface, and have no overlying epithelial defect compared with infectious infiltrates. 38 The treatment of suture-related infections begins with removal and culture of the suture. Running sutures pose a particular challenge as premature removal of the suture prior to proper would healing can lead to wound dehiscence.…”
Section: Suture-related Complicationsmentioning
confidence: 99%
“…Early diagnosis of corneal graft rejection and/or failure has been a challenge for many researchers, and histological in vivo and ex vivo studies have demonstrated progress on this issue [610]. However, studies regarding the Descemet's membrane (DM, the true basal membrane of the cornea) remain scarce.…”
Section: Introductionmentioning
confidence: 99%